Transactions commerciales et relations sociales entre Grecs et Turcs de Bruxelles - Katerina Seraïdari (Brussels Studies, 2011)
This article examines how the extent to which Greeks and Turks “live together” in Brussels can be measured by means of commercial transactions. The question is knowing what the impact of monetary exchanges on the symbolic borders between these social groups is and how these exchanges have changed over time. Whereas the market interactions between Greeks and Turks in the years that followed their moving to Brussels were defined by the attitude of affinity (out of conviction or necessity), those that occur today belong more to the framework of an urban cosmopolitanism defined by the attitude of indifference. Even if the commercial transactions constitute an area for hierarchizing the players, they also operate as a place of encounters or confrontation, where each person reinterprets his or her own national past and positions her/himself with regard to the legacy of the Greco-Turkish conflict and its representations.